PENGARUH MODAL KERJA, PROFITABILITAS, KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bachtiar Rahman Halik; Ucik Lutfiyah Nor; Pujianto Pujianto (Income, 2022)
This study aims to determine the effect of Working Capital, Profitability,Financial Performance on Stock Prices. The independent variables in this study are working capital,Profitability (ROA), Financial Performance (CR).The sampling technique in this study is purposive sampling, with the population in the basic and chemical industry deposit manufacturing companiesas many as 8 companies, data analysis used in the form of data normality test, classical assumption test, multiple linear analysis, t test, f test, and multiple determination coefficient testWorking capital has a significant effect on stock prices, profitability has a positive and significant effect on stock prices, and financial performance has no effect on stock prices